The Effects of Occupational Knowledge: Job Information Centers, Educational Choices, and Labor Market Outcomes - Nils Saniter; Thomas Siedler (Institute for the Study of Labor (IZA), 2014)
This study examines the causal link between individuals' occupational knowledge, educational choices, and labor market outcomes. We proxy occupational knowledge with mandatory visits to job information centers (JICs) in Germany while still attending school. Exogenous variation in the location and timing of JIC openings allow estimating causal effects in a difference-in-difference setup. Combining linked survey-administrative data with data on JICs permits to detect whether individuals benefited from the comprehensive information service when they were young. The results suggest that individuals, who went to school in administrative districts with a JIC, have higher educational attainments and a smoother transfer to the labor market than students who did not have access to these facilities. However, we find no effects on individuals' earnings in their first job or later in life. Overall, our results confirm the importance of policies that promote occupational knowledge among young adults.
Keywords: I2; J24; J31; 330; education; uncertainty; job matching; information; job information centers